Predominant cerebellar phenotype in spastic paraplegia 7 (SPG7) - Yahikozawa, Hiroyuki (Hum Genome Var, 2015)
We report a Japanese family with spastic paraplegia 7 (SPG7) that carries a deleterious homozygous p.R398X mutation in SPG7. The patients showed a predominant cerebellar ataxia phenotype. SPG7 is quite rare in Japan, but it should be included in the differential diagnosis for hereditary spastic-ataxic syndromes, even if the cerebellar signs are much more pronounced than the pyramidal tract signs.